Genetic editing of colonic organoids provides a molecularly distinct and orthotopic preclinical model of serrated carcinogenesis. Issue 4 (17th April 2018) - Lannagan, Tamsin R M; Lee, Young K; Wang, Tongtong; Roper, Jatin; Bettington, Mark L; Fennell, Lochlan; Vrbanac, Laura; Jonavicius, Lisa; Somashekar, Roshini; Gieniec, Krystyna; Yang, Miao; Ng, Jia Q; et al.
Abstract : Objective: Serrated colorectal cancer (CRC) accounts for approximately 25% of cases and includes tumours that are among the most treatment resistant and with worst outcomes. This CRC subtype is associated with activating mutations in the mitogen-activated kinase pathway gene, BRAF, and epigenetic modifications termed the CpG Island Methylator Phenotype, leading to epigenetic silencing of key tumour suppressor genes. It is still not clear which (epi-)genetic changes are most important in neoplastic progression and we begin to address this knowledge gap herein. Design: We use organoid culture combined with CRISPR/Cas9 genome engineering to sequentially introduce genetic alterations associated with serrated CRC and which regulate the stem cell niche, senescence and DNA mismatch repair. Results: Targeted biallelic gene alterations were verified by DNA sequencing. Organoid growth in the absence of niche factors was assessed, as well as analysis of downstream molecular pathway activity. Orthotopic engraftment of complex organoid lines, but not Braf V600E alone, quickly generated adenocarcinoma in vivo with serrated features consistent with human disease. Loss of the essential DNA mismatch repair enzyme, Mlh1, led to microsatellite instability. Sphingolipid metabolism genes are differentially regulated in both our mouse models of serrated CRC and human CRC, with key members of this pathway having prognostic significance in the human setting. Conclusion: We generate rapid, complex models of serrated CRC to determine the contribution of specific genetic alterations to carcinogenesis. Analysis of our models alongside patient data has led to the identification of a potential susceptibility for this tumour type.